The Influence of Job Satisfaction and Work-Family Balance on Employee Performance - Rhima Sugi Prabandari; Gesti Purnama Sari; Edy Raharja (LifeSciFi, 2025)
Employee performance is a crucial factor in determining the success of an organization. Optimal performance contributes to increased productivity, efficiency, and the company’s competitiveness. Therefore, it is important for companies to understand the factors that can influence employee performance, such as job satisfaction and work-family balance. This study aims to analyze the influence of job satisfaction and work-family balance on employee performance. Employee performance is a crucial element in achieving organizational goals and is influenced by various psychological and social factors. Job satisfaction fosters comfort, loyalty, and motivation at work, while work-family balance helps employees maintain harmony between professional responsibilities and personal life, contributing to emotional stability and productivity. This research uses a quantitative approach with survey methods and regression analysis to examine the relationship between variables. The results show that job satisfaction and work-family balance have a positive and significant effect on employee performance. These findings highlight the importance of organizational attention to employee well-being and personal life as part of efforts to enhance overall performance.